Disidentification, (Non)Normativity and the Gothic in Contemporary Latin American Women's Writing - Mendes, Rafael (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Hispanic Studies, 2026)
This thesis explores ways to resist normative regulation in a representative sample of literary texts by six contemporary Latin American women writers. Deploying an interdisciplinary framework informed by queer/cuir studies and decolonial feminisms, this thesis asserts that these writers recast the Anglo-American Gothic genre to participate in and narrate the contemporary struggle against intersectional forms of oppression, particularly those stemming from cisheteropatriarchy. Using `monstrosity' and `the female grotesque' as key analytical categories, this thesis demonstrates how normative codes are transgressed from within as strategies of disidentification. By understanding identity as a relational process, this thesis posits that in the texts, coalition politics are formed and enacted in favour of subaltern individuals without essentialising in-group differences. Overall, this thesis presents a new roadmap for Latin American Studies by situating the literary output of six contemporary women writers within the Gothic tradition, interweaving gender, feminist, and decolonial perspectives.
APPROVED
Keywords: Latin American Gothic; Disidentification; Gender Studies; Queer/cuir; Monster; Latin American Literature; Latin American women's writing; Divanize Carbonieri; Camila Sosa Villada; Mariana Enriquez; Maria Fernanda Ampuero; Monica Ojeda; Fernanda Melchor